The fall and rise of Diopatra in Southern Brazilian sandy beaches - Paiva, Paulo Cesar; Amaral, Antonia Cecilia Zacagnini; Seixas, Victor Correa; Petti, Mônica Angélica Varella; Steiner, Tatiana Menchini (Frontiers in Ecology and Evolution, 2025)
High-density Diopatra populations were recorded in the South Brazilian Bight in the 1970s and 1980s. However, by the 1990s, intertidal populations had declined sharply. The decline and partial recovery raise questions about the factors driving long-term changes in abundance. To better understand these shifts, patches of Diopatra species from Brazilian sandy beaches were followed for 50 years. Data were accessed from papers, gray literature, images, and collections to verify time changes in the South Brazilian Bight (SBB) from 1974 to 2023. We modeled maximum density over time at 15 beaches, observing very high densities (>100 ind.m−2) in 1974 followed by a decrease (~10 ind.m−2) of three species of Diopatra until 1995 and a strong decline (1996–2002) when populations were almost regionally extinct (0–2ind.m−2). A recovery (3–20 ind.m−2) occurred after 2006 for D. victoriae and D. marinae, the latter associated with warmer northern waters, suggesting a range shift. This pattern was associated with heatwaves linked to an El-Niño event (1988) and a gradual SST surface warming of ca. 1°C since 1974. The usage of Diopatra spp. as fishing bait could also be associated with such a reduction. After 2016, D. neapolitana, a likely alien species, was established in the SBB in high densities. Projections based on species distribution modeling (SDM) suggest a potential of invasion in the same range of the known species of D. cuprea complex along the Brazilian coast despite that there are no signs of competition between both species.